Development of Pop-Up Book Based Learning Media on Optical Instruments Material in Senior High School/Islamic Senior High School - Zahara, Laxmi; Khadijah, Siti Laili; Wajdi, Badrul (Impulse: Journal of Research and Innovation in Physics Education, 2024)
Learning media makes the teaching and learning process easier and increases students' interest in learning. This development research developed a pop-up book-based learning media on optical devices material for Senior High School/Islamic Senior High School. This type of research is research and development research. The development model used in this research is the 4D model: define, design, develop, and disseminate. Product testing of pop-up book- based learning media development applied validation from material experts and media experts, subject teachers and student response questionnaires. Technical analysis of data from the distribution of questionnaires was done by tabulating data from each validator and calculating the percentage. Data collection techniques use instruments in the form of interviews, sheets validation, questionnaire, and pretest-posttest. The researchers analyzed the obtained data using the formula for determine the percentage of product feasibility. Based on the assessment results of 2 material experts, 2 media experts and 2 teachers, it shows that pop up books are included in the very feasible category. Meanwhile, the student response assessment was included in the very good response category and the results of the effectiveness test showed the quite effective category.